Psoralea Corylifolia Conservation by Tissue Culture and Enhancement of Secondary Metabolites with Homoeopathy: A Narrative Review (Advancements in Homeopathic Research, 2024)
India has an extremely diverse range of  plants, many of which have therapeutic applications.  The rich resource is being over-exploited and is  diminishing at an alarming rate. Therefore, it is crucial  to adopt strategies for the sustainable management of  resources derived from traditional medicinal plants.  The diverse array of secondary metabolites found in  plants not only imparts therapeutic effects but also  forms the cornerstone of medicinal advancements in  pharmaceutical formulations.
Keywords: Homoeopathy; Agrohomoeopathy; Micropropogation; Plant tissue culture